Changes in the Diagnostic Efficiency of Thyroid Fine-Needle Aspiration Biopsy during the Era of Increased Thyroid Cancer Screening in Korea - Lee, Young Ki; Park, Kyeong Hye; Song, Young Duk; Youk, Taemi; Nam, Joo Young; Song, Sun Ok; Shin, Dong Yeob; Lee, Eun Jig (Cancer research and treatment, 2019)
The volume of thyroid cancer screening and subsequent thyroid fine-needle aspiration (FNA) have rapidly increased in South Korea. We analyzed the thyroid cancer diagnoses/thyroid FNA ratio according to the annual number of FNA to evaluate changes in the diagnostic efficiency of FNA. This was a nationwide population-based retrospective cohort study. The overall thyroid cancer diagnoses/thyroid FNA ratio and annual incremental thyroid cancer diagnoses/incremental thyroid FNA ratio were indirectly calculated using data obtained from the Korea Central Cancer Registry database and the Korean National Health Insurance Service claims database from 2004 to 2012. Pearson correlation analyses were performed to evaluate the strength of linear associations between variables. The number of thyroid FNA increased from 28,596 to 177,805 (6.2-fold increase) from 2004 to 2012. The overall thyroid cancer diagnoses/thyroid FNA ratio decreased from 36.5% in 2004 to 25.1% in 2012 and was negatively correlated to the number of FNA (R=‒0.977, p < 0.001). The annual incremental thyroid cancer diagnoses/incremental thyroid FNA ratios (range, 15.3% to 30.7%) were always lower than the overall thyroid cancer diagnoses/thyroid FNA ratio in each year and also worsened according to the increase in the number of FNA (R=‒0.853, p=0.007). The diagnostic performance of both overall and annual incremental thyroid FNA worsened, whereas the number of thyroid FNA procedures increased. More sophisticated indications for FNA are required to improve its diagnostic efficiency, considering the increased burden of screening-detected thyroid nodules.